Neurosurgical review : for daily clinical use and oral board preparation - Zerris, Vasilios A. (Thieme, 2020)
Robust ABNS exam prep and didactic review of the entire spectrum of neurosurgery from A to Z The American Board of Neurological Surgery oral examination has undergone periodic review and revision over the years, with a new format instituted in spring 2017. This review book is specifically geared to the new format. The ABNS oral examination process is relevant, rigorous, and of value to the neurosurgical specialty and the public, ensuring neurosurgeons meet the highest standards of practice. Neurosurgical Review: For Daily Clinical Use and Oral Board Preparation by Vasilios A. Zerris and distin.